CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF BRUCELLIOSIS IN WOMEN OF FERTIL AGE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The epidemiological situation of brucellosis in Uzbekistan is concerning due to ongoing epizootics among cattle, the main source of infection for humans. Brucellosis remains a prevalent zoonotic disease, with urogenital manifestations in both men and women. This study aimed to investigate the clinical and epidemiological characteristics of brucellosis in women of childbearing age in the Kashkadarya region. Medical records of 110 women with brucellosis treated at the Kashkadarya Regional Infectious Diseases Hospital in 2019 were retrospectively analyzed. The highest morbidity rates were observed in certain districts, with a peak in May-June. The predominant transmission route was through direct contact, followed by ingestion. Acute brucellosis was characterized by fever, joint pain, and positive serological tests, while the subacute form presented with musculoskeletal symptoms. Chronic brucellosis patients exhibited asthenic and articular syndromes, along with reproductive organ involvement. This study provides valuable insights into the epidemiology and clinical presentation of brucellosis in women in the Kashkadarya region, highlighting the importance of effective prevention and control strategies.